EFISIENSI PEMASARAN SUSU PASTEURISASI DI CV. CITA NASIONAL KABUPATEN SEMARANG - Parida S.A. Sihombing; T Ekowati; W Sumekar (Universitas Wahid Hasyim, 2016)
The purpose of this research was to analyse the implementation of marketing (distribution pattern, marjin and marketing efficiency) pasteurized milk in CV. Cita Nasional. Research method used case study. Techniques data collection of the research was interview manager of a company with the guidelines the questionnaire. The result of the research showed CV. Cita Nasional used two distribution patterns pasteurized milk. Pasteurized milk pack 150 ml using pattern producer - agents - retailers – consumers and pasteurized milk pack 170 ml using pattern producer – consumers. In a pattern producer - agents - retailers – consumers in 2011 obtained marketing marjin IDR. 1,405/cup, in 2012 was IDR. 1,348/cup and in 2013 was IDR. 1,312/cup. Marketing efficiency pattern producer - agents - retailers – consumers in 2011 was 43.78 %, in 2012 was 46.06 % and in 2013 47.51 %. Marketing marjin in a pattern producer – consumers in 2011 was IDR. 969/cup, in 2012 was IDR. 889/cup and in 2013 was IDR. 871/cup. Marketing efficiency pattern producer – consumers in 2011 was 51.51 %, in 2012 was 55.54 % and in 2013 was 56.4 %. Keywords: distribution pattern, marjin, marketing efficiency, milk, pasteurized